Analisis Pengaruh Komisaris Independen, Kompensasi Rugi Fiskal, Leverage, Profitabilitas dan Ukuran Perusahaan Terhadap Tax Avoidance(Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2012-2015) - Milhanudin, Arip, Dr. Noer Sasongko, S.E, M. Si, Akt, CA (2017)
This research aimed to examine the effect of independent commissioner, compensation tax losses, leverage, fitability and firms size as independent variables on tax avoidance as the dependent variable. This research was conducted using secondary data. The population in this research is facturing company listed on the indonesia stock exchange in the periode 2012-2015. The research used purposive sampling technique and found 138 companies. The analytical method used is multiple linear regression analysis by first doing a classic assumption test including normality ,lticollinearity test, autocorrelation test, heterocedasticity test, and hypothesis testing are used is adjusted R Square, F test and t test. The results of this research indicate that only profitability variable that effects tax ance.Simultaneously, variables independent commissioner, compensation tax losses, leverage, profitability and firms size effect tax avoidance. Keywords: Independent Commissioner, Compensation Tax Losses, Leverage, Profitability, Firms Size, Tax Avoidance.